2019
DOI: 10.1155/2019/6309160
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Engineering Application of Coalbed Water Injection

Abstract: Coalbed water injection is the most basic and effective dust-proof technology in the coal mining face. To understand the influence of coalbed water injection process parameters and coalbed characteristic parameters on coal wetting radius, this paper uses Fluent computational fluid dynamics software to systematically study the seepage process of coalbed water injection under different process parameters and coalbed characteristic parameters, calculation results of which are applied to engineering practice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Currently, the main dust prevention methods in underground coal mine include preinjection of water into coal, ventilation, exhausting of dust, purification of air by dust remover, spraying, and dust isolation via enclosing [19][20][21][22][23][24][25]. Spraying has been extensively applied in underground mines for dedusting due to the low cost, convenient operation, and practicability [26][27][28][29][30][31]. e results in previous studies also revealed that the dust-suppression efficiency via spraying was closely related to the wettability of the coal dust.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, the main dust prevention methods in underground coal mine include preinjection of water into coal, ventilation, exhausting of dust, purification of air by dust remover, spraying, and dust isolation via enclosing [19][20][21][22][23][24][25]. Spraying has been extensively applied in underground mines for dedusting due to the low cost, convenient operation, and practicability [26][27][28][29][30][31]. e results in previous studies also revealed that the dust-suppression efficiency via spraying was closely related to the wettability of the coal dust.…”
Section: Introductionmentioning
confidence: 97%
“…Zhen Liu et al [3] pointed out that the structure and seepage characteristics of coal samples around the borehole determine the effect of water injection. Yijie Shi et al [4] used Fluent to discuss the influence of water injection process parameters such as water injection time, water injection pressure, wellbore diameter and characteristic parameters of coalbed methane on the wetting radius. Jianlong Li et al [5] believed that wetting agents are usually used to improve the efficiency of mine dust water injection.…”
Section: Introductionmentioning
confidence: 99%
“…The airflow from the side air outlet forms a shielding air curtain on the roadway to prevent the spread of dust and improve the dust-catching effect of the air inlet. The wall-attached air duct can greatly improve the working environment of the fully mechanized excavation face, prevent gas accumulation on the top of the roadway, and ensure the safe production of the mine [25,26]. However, the radial air curtain produced by the wallattached air duct has a relatively weak rotation ability, and it is very easy to form a hollow air curtain due to the serious impact of the roadway environment.…”
Section: Introductionmentioning
confidence: 99%